Transformasi Pendidikan Agama Islam di Era Revolusi Industri 4.0: Strategi Menghadapi Tantangan Teknologi Digital dan Inovasi - Nur Sakinah Siregar; Putri Salehah Siregar; Gusmaneli Gusmaneli (Populer: Jurnal Penelitian Mahasiswa, 2024)
This journal discusses learning strategies and the definition of Islamic religious education, as well as education in the era of revolution 4.0. Learning strategies include choosing appropriate methods for delivering religious material, taking into account teaching principles and student characteristics. Islamic religious education aims to form religious individuals by wisely inviting and developing affective attitudes. The era of revolution 4.0 demands changes in education by integrating 21st century competencies and digital technology. Islamic education also faces challenges such as cultural backwardness, negative stigma, and political dualism, which require solutions in the form of reform and renewal. Teachers in this era need to have various competencies to face changing times, such as comprehensive assessments, 21st century skills, online modules, and authentic and innovative learning. Overall, Islamic education needs to continue to adapt to technological developments and the needs of the times to produce quality human resources ready to face the future.